INFLUENCE OF EXTRA-CLASS ACTIVITIES ON THE ORGANISM OF CHILDREN AND ADOLESCENTS ON THE DISCIPLINE OF PHYSICAL CULTURE (Scientific journal of the Fergana State University, 2023)
In the article, the analysis of special literature related to the effect of physical exercises on the functional state of the body and the content of special theoretical knowledge and practical skills related to the problem in the lifestyle of students of our country is systematized. It is intended for future bachelors, masters, school social education teachers and sports coaches.